BENEFICIATION OF BOREHOLE IRON ORE SAMPLES THROUGH MULTI-STAGES MAGNETIC SEPARATION - Nuryadi Saleh; Nngurah Ardha (Puslitbang tekMIRA, 2015)
This study investigates the effectiveness of magnetic concentration techniques for the beneficiation of borehole samples of Arasuko - West Sumatera iron ore. It is a low-grade type of ore sample (±35% Fe) with high silica and calcium content (±36%). Based on the fact, that there are appreciable differences in magnetic susceptibility between the desired iron minerals and the gangue minerals, hence, it was suggested that multi-stages magnetic separation may be useful to concentrate this type of ore. Because of the fine dissemination of the iron minerals and the most abundant gangue mineral, the particles size of ore was set at 80% passing 150 meshes. Rougher tests of magnetic separation produced concentrates with iron content of about 58.2% Fe; the tailing of rougher stage was then scavenged using higher magnetic intensity. Further, the rough and scavenged concentrates were mixed and fed into a cleaner stage with low magnetic intensity. Results indicate that the final iron concen- trate assaying of 68.1% Fe at a recovery of about 80% is achieved and reckoned as an iron premium-grade concentrate.